Telling Tales The Impact of Germany on English Children's Books 1780-1918 - Blamires, David (Open Book Publishers, 2009)
Germany has had a profound influence on English stories for children. The Brothers Grimm, The Swiss Family Robinson and Johanna Spyri's Heidi quickly became classics but, as David Blamires clearly articulates in this volume, many other works have been fundamental in the development of English children's stories during the 19th century and beyond. Telling Tales is the first comprehensive study of the impact of Germany on English children's books, covering the period from 1780 to the First World War. Beginning with The Adventures of Baron Munchausen, moving through the classics and including many other collections of fairytales and legends, it covers a wealth of translated and adapted material.